2012
DOI: 10.1002/esp.3306
|View full text |Cite
|
Sign up to set email alerts
|

Wind direction and complex sediment transport response across a beach–dune system

Abstract: Evidence from a field study on wind flow and sediment transport across a beach–dune system under onshore and offshore conditions (including oblique approach angles) indicates that sediment transport response on the back‐beach and stoss slope of the foredune can be exceedingly complex. The upper‐air flow – measured by a sonic anemometer at the top of a 3·5 m tower located on the dune crest – is similar to regional wind records obtained from a nearby meteorological station, but quite different from the near‐surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
113
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 61 publications
16
113
1
Order By: Relevance
“…3C). Indeed, Arens et al (17) and Bauer et al (18) reported no transport activity during favorable wind conditions on the windward side of steep dunes (∼27°and ∼22°respectively; 3C). In contrast, flatter foredunes have room to grow, as those in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3C). Indeed, Arens et al (17) and Bauer et al (18) reported no transport activity during favorable wind conditions on the windward side of steep dunes (∼27°and ∼22°respectively; 3C). In contrast, flatter foredunes have room to grow, as those in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical finding that foredune size correlates with beach type, with foredunes up to 10 times higher on dissipative beaches than on reflective ones (1, 2), combined with conceptual models that predict enhanced aeolian transport on dissipative beaches (1,14,15), has motivated the common assumption that maximum foredune size is primarily controlled by sand supply (1,4,15,16). However, this explanation is problematic based on reports of large foredunes on dissipative beaches with a negligible sand input (17,18) and findings of very small foredunes formed on a reflective beach under high sand supply (19). In addition, there seems to be no general empirical relation between foredune size and beach morphology, i.e., beach width and slope (15,20,21), characteristics traditionally used, along with grain size, as a proxy for potential sand transport (which is notoriously difficult to measure at the beach).…”
mentioning
confidence: 99%
“…In a subsequent study at the PEI site, Bauer et al (2012) documented pronounced deflection of oblique incident winds over the foredune, and found that wind directions on the beach during a storm event were far less variable than those on the dune crest for the same incident winds. During alongshore incident flow conditions Lynch et al (2009) found that wind near the dune crest was deflected more offshore compared to the flow along the beach and, for obliquely onshore winds, they found a deflection of ~20° towards shore-normal.…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
“…Davidson-Arnott et al, 2003Walker et al, 2003Walker et al, , 2006Hesp et al, 2005Hesp et al, , 2009Hesp et al, , 2013Bauer et al, 2009Bauer et al, , 2012Delgado-Fernandez and Davidson-Arnott, 2009;Hesp and Walker, 2012;Chapman et al, 2012Chapman et al, , 2013DelgadoFernandez et al, 2013;Ollerhead et al, 2013). The foredune crest is ~10 m above mean water level with a steep stoss slope (20°-25°) and an ENE-WSW crestline orientation.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation